Utilization of the coastal area of Miangas Island as the outermost small island of Indonesia - Achmad Nagi; Gandhi Napitupulu; Isdradjad Setyobudiandi; Mujizat Kawaroe; Jamaluddin Jamaluddin (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
Miangas Island is one of the outer islands of Indonesia. Determining policies for optimal and sustainable spatial use of coastal areas on Miangas Island requires a deep understanding of the people who live there. Observation survey and interview methods were used to collect primary data. The analysis used is the Analytical Hierarchy Process (AHP) to formulate solutions to land use conflicts in coastal and marine areas. The results of the analysis of conflict resolution on the use of coastal space using AHP show that the criteria that have a large influence on the purpose of conflict resolution analysis are land availability and suitability, and the first priority for alternative spatial development for the coastal area of Talaud Islands Regency is the development of fishery areas.